A Survey of Audiovisual Materials for Asian History Subjects - Alegre, Kristel Ann; Legaspi, Carlos Eduardo I. (Technium Social Sciences Journal, 2021)
Audiovisual materials are essential in education. Audiovisual materials are devices that are used in classrooms to encourage the teaching-learning process and make it easier and interesting. Audiovisual materials are the best tools for making teaching effective and the best devices for the dissemination of knowledge. It has been predicted that by 2020, teachers should be technology-driven and should transform the classrooms into learning hubs. The teacher and the whole system must change from teaching to learning. The teacher must journey with the student through technology. Hence, the researcher was motivated to conduct this study to prepare an in-depth analysis of the audiovisual materials used by teachers in their Social Science classes. The study aimed to determine and classify available Online Audio-Visual Materials available in YouTube. The output of the study is a Catalog of online Audio-Visual Materials for Asian History available on YouTube. This catalog contains an in-depth analysis showing the connection of the materials to the learning outcomes specified in the curriculum and some Enrichment activities. A descriptive analysis was used to analyze the data. The data and information were gathered and secured for further analysis and assessment of information about the audiovisual materials.